2013
DOI: 10.7567/apex.6.036601
|View full text |Cite
|
Sign up to set email alerts
|

GaN Thin Film Based Light Addressable Potentiometric Sensor for pH Sensing Application

Abstract: Gallium nitride (GaN) is a material with remarkable properties, including wide band gap, direct light emission and excellent chemical stability. In this study, a GaN-based light addressable potentiometric sensor (LAPS) with Si 3 N 4 50 nm as a sensing membrane is fabricated. By modulated optical excitation from an ultraviolet 365 nm light-emitting diode, the photoresponse characteristic and related pH sensitivity of the fabricated GaNbased LAPS is investigated. A Nernstian-like pH response with pH sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…It could be observed that the influences of interfering N + and K + ions on the studied ISFET are negligible. Comparisons of pH sensing performance among Device A and previously reported works are listed in Table 2 [20][21][22][23][24][25][26]. Although the highest average sensitivity (54.88 mV/pH) of treated ISFET is not outstanding as compared to previous works, the pH sensing performance is remarkably enhanced (∼26% improvement) by a simple H 2 O 2 surface treatment.…”
Section: Resultsmentioning
confidence: 92%
“…It could be observed that the influences of interfering N + and K + ions on the studied ISFET are negligible. Comparisons of pH sensing performance among Device A and previously reported works are listed in Table 2 [20][21][22][23][24][25][26]. Although the highest average sensitivity (54.88 mV/pH) of treated ISFET is not outstanding as compared to previous works, the pH sensing performance is remarkably enhanced (∼26% improvement) by a simple H 2 O 2 surface treatment.…”
Section: Resultsmentioning
confidence: 92%
“…On the other hand, electrochemical methods are typically straightforward and inherently quantitative, and require simpler operation and setups. Electrochemical methods, however, have downsides, such as long-term instability and vulnerability to electrode fouling, but nevertheless, they are the most commonly used methods for pH detection, whereby the potential (potentiometric) [20,21,[51][52][53][54][55][56], current (amperometric) [57][58][59][60][61][62][63], or charge in an electrochemical cell serve as the analytical signals. Indeed, the glass electrode is currently the most commonly used electrochemical sensor for potentiometric pH measurements.…”
Section: Ph Sensing Mechanismmentioning
confidence: 99%
“…GaN is a wide-band-gap semiconductor (3.4 eV at 300 K), and it is known to be a promising material for chemical sensor applications with remarkable properties including excellent chemical stability and biocompatibility [12,13]. As was demonstrated, various reducing and oxidizing gases like carbon monoxide (CO), hydrogen (H 2 ), acetylene (C 2 H 2 ) and nitric oxides (NO and NO 2 ) can be tested using heterostructured GaN thin films [14][15][16], hydrogen (H 2 ) and nitrogen dioxide (NO 2 ) can be detected using GaN nanowires in previous researches [1,17,18].…”
Section: Introductionmentioning
confidence: 99%